2021
DOI: 10.1016/j.ejvs.2021.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Octogenarians and the Effect of Comorbidities After Intact Abdominal Aortic Aneurysm Repair in the Netherlands: A Nationwide Cohort Study

Abstract: WHAT THIS PAPER ADDS This paper examined retrospectively the outcomes of octogenarians that underwent either open surgical repair or endovascular repair for an intact abdominal aortic aneurysm in an obligatory nationwide registry, reflecting daily clinical practice in the Netherlands. The study showed that besides an increased age, comorbidities were clearly associated with impaired peri-operative survival after both open surgical and endovascular repair.Objective: Age is an independent risk factor for mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…However, our results were similar to those from the EUROSTAR data, which showed that the complication rate was somewhat higher among octogenarians compared with that among younger patients. 9 A similar pattern was also reported by Alberga et al 16 who observed a statistically significant higher rate of major complications after EVAR in octogenarians compared with nonoctogenarians.…”
Section: Discussionsupporting
confidence: 80%
“…However, our results were similar to those from the EUROSTAR data, which showed that the complication rate was somewhat higher among octogenarians compared with that among younger patients. 9 A similar pattern was also reported by Alberga et al 16 who observed a statistically significant higher rate of major complications after EVAR in octogenarians compared with nonoctogenarians.…”
Section: Discussionsupporting
confidence: 80%
“…Besides advanced age and presence of cardiac, pulmonary, and renal comorbidities, frailty and preoperative functional status are predictors of postoperative morbidity and mortality [ 302 , 303 , 304 ]. Female sex, aneurysm diameter, and smoking habits are also associated with poor long-term survival.…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…Advanced age is a well known risk factor for peri-operative death after AAA surgery, 10 , 11 , 12 , 13 and particularly dangerous when accompanied by comorbidity. The impact of comorbidities was demonstrated in a study showing a 14.8% mortality risk after AAA repair in octogenarians with comorbidities vs. 3.8% in octogenarians without comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of comorbidities was demonstrated in a study showing a 14.8% mortality risk after AAA repair in octogenarians with comorbidities vs. 3.8% in octogenarians without comorbidities. 10 …”
Section: Discussionmentioning
confidence: 99%